Prognostic Effect of Primary Recurrence Patterns in Squamous Cervical Carcinoma After Radical Surgery - Zhang, Zongkai; Jiang, Long; Bi, Rui; Wu, Xiaohua; Ke, Guihao; Zhu, Jun (Frontiers in Oncology, 2022)
Objective To examine the effect of primary recurrence patterns on the prognosis of squamous cervical cancer after initial treatment. Methods Primary recurrence patterns and prognostic factors were examined in stage IB-IIA cervical cancer patients after initial treatment. Recurrence site (locoregional recurrence and distant metastasis or in-field and out-field recurrence for patients receiving adjuvant radiotherapy) and subtype (nodal and organ recurrence) were examined. Clinicopathological characteristics and survival rates were evaluated to generate a prognostic nomogram. Results A total of 472 patients were included. The median follow-up period, 5-year overall (OS) rate, and median OS were 59.1 months, 33.7%, and 24.0 months, respectively. Overall, 38.8% and 61.2% of the patients had locoregional recurrence and distant metastasis, respectively, and survival rates were comparable in these groups. Patients with nodal recurrence had better OS than those with organ recurrence (38.3% vs 30.7%, respectively; P = 0.001). Patients not receiving adjuvant radiotherapy had increased risk of pelvic recurrence [odds ratio (OR) = 0.148; 95% confidence interval[(CI): 0.075–0.291, P = 0.000]. Positive lymph-vascular space invasion (OR= 1.928; 95% CI: 1.151–3.229, P = 0.013) and no chemotherapy (OR = 0.521; 95% CI: 0.317–0.733, P = 0.040) increased the risk of distant metastasis. Positive lymph node status after initial treatment were associated with nodal recurrence (OR = 3.729; 95% CI: 1.838–7.563, P = 0.000), while elevated preoperative squamous cell carcinoma antigen (SCC-Ag) levels were associated with organ recurrence (OR = 1.642; 95% CI: 1.325–2.265, P = 0.002). Recurrence subtype, therapy for relapse, the International Federation of Gynecology and Obstetrics stage, adjuvant radiotherapy, preoperative SCC-Ag levels, and risk subgroup were independently associated with OS. Conclusions Primary recurrence patterns were associated with specific clinicopathological characteristics of cervical cancer. Recurrent cervical cancer prognosis was mainly affected by recurrence location and subtype.